STRATEGI INDONESIA DALAM MENANGANI PANDEMI COVID-19 MELALUI FOREIGN POLICY AND GLOBAL HEALTH INITIATIVES TAHUN 2020 - Alfiana Nur Az Zahra (2022)
This study aims to discuss Indonesia's health diplomacy in dealing with the Covid-19 pandemic through the Foreign Policy and Global Health (FPGH) Initiatives in 2020 using the concepts of global health diplomacy and health security. The method used in this research is descriptive qualitative by obtaining data from secondary data of literature studies through books, scientific journals, articles, and news contained diplomatic activities in pandemic response. The author uses three stages of data analysis of the Interactive Model from Miles and Huberman, condensation, data presentation, and withdrawal conclusion and verification. The results shows that Indonesia's diplomacy through FPGH in 2020 aims to provide affordable healthcare and ensure the availability of vaccines as handling the pandemic. The Covid-19 pandemic has consciously increased collaboration in dealing with inequality and gap in various aspects. This involves multilateral cooperation as the main factor in realizing global health security. These activities are shown through international meetings such as the UN General Assembly, WHO, WHA, and ASEAN. The collaboration also implicates the COVAX Facility to ensure equity amd equitable distribution of vaccines.